Natural estuarine cycles of nocturnal hypoxia significantly reduce growth rates of North Atlantic bivalves - Kraemer, Jeffrey; Gobler, Christopher J. (Frontiers in Marine Science, 2025)
Bivalves are economically and ecologically important species and the estuarine systems they inhabit can experience diel fluctuations in dissolved oxygen (DO) as a result of the shifting balance between photosynthesis and respiration. During warmer summer months, these fluctuations are often intensified, potentially exposing local bivalve populations to repeated episodes of hypoxia. For this study, in situ flow-through experiments tested the effects of naturally-occurring nocturnal hypoxia on early life stage bivalves. Juvenile bivalves (hard clams, M. mercenaria; Eastern oyster, C. virginica; and bay scallop, A. irradians) were subjected to either natural estuarine cycles of DO and pH or amended, static normoxic but still acidified conditions during the peak cycling season (summer). Growth and survival rates of bivalves were quantified. During nine experiments across three summers, nocturnal hypoxia in unamend controls was moderate, with, on average, 3 hours per night of DO below 3 mg L-1, 1 hour per night of DO below 1 mg L-1, and a mean nocturnal DO concentration of 4.7 mg L-1. Still, amelioration of this nocturnal hypoxia during experiments yielded a mean increase in bivalve growth of 20% (range: 0 - 70%). Hard clams were more resilient to bouts of nocturnal hypoxia than scallops and oysters. The percent increases in growth rates of the hypoxia-ameliorated, aerated treatments were significantly correlated with hours of hypoxia during experiments (p<0.0001) and were significantly and inversely correlated with average nocturnal DO concentrations in control treatments (p<0.001). Application of these relationships to DO patterns at 19 sites across NY during summer indicated nocturnal hypoxia at these locales may have repressed bivalve growth rates by 10 – 240%. Given the enhanced predation pressure experienced by smaller bivalves, the slowed growth of unamended controls demonstrates that even small bouts of nocturnal hypoxia are a threat to estuarine bivalve populations.